ISSUES OF DEVELOPMENT AND MANAGEMENT OF METHODOLOGY OF TEACHING PHYSICS IN GENERAL SCHOOLS BASED ON ARTIFICIAL INTELLIGENCE - Allaniyazova Bibigul Sarsenbay qizi (Prospects for innovative technologies in science and education, 2026)
This article examines the issues of effective management of the use of artificial intelligence technologies in the process of developing the methodology of teaching physics in general schools. The main goal of the study is to improve the methodological and management mechanisms for integrating educational tools based on artificial intelligence into the process of teaching physics. The study used literature analysis, pedagogical observation, comparison and empirical analysis methods. The results showed that the systematic and controlled use of artificial intelligence significantly increases the level of mastery of physical concepts and practical skills of students.